(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
One of the reasons Philip Larkin is maligned so harshly is because he is so easily understood, or at least appears to be so without exerting much effort to glean any deeper meaning from his poems. There is no respite from the drudgery of everyday life that can be found in literature for a short time in his work. It is Philip Larkin’s life and work that are the subject of this essay.